Improving English Spoken Skills through Self Recorded Video for Higher Education Students - Nita Henita Koesoemah (Jurnal Bahasa Inggris Terapan, 2019)
The research is aimed to analyze the improvement of English speaking skills for higher education students by means of Self Recorded Video. The focus of this research is on four speaking skill categories; Pronunciation, Vocabulary, Grammar and Fluency. The recorded videos are analyzed.To get the answer of the aims, descriptive method is used. The data is students’ self recorded videos which were done  in one semester (semester 1). The result obtained is that practising speaking English through self-recorded video can improve student speaking skills. The improvement can be in one or more categories.Keywords: fluency, self-recorded video, descriptive method